Optical properties of quantum-sized structures and two-dimensional photon crystals fabricated in semiconductor substrates using irreversible giant modification - Kamuz, A.M.; Oleksenko, P.F.; Kamuz, O.A.; Ilin, O.A.; Stronski, A.V. (Functional Materials, 2008)
It is known that using the irreversible giant modification, it is possible to change locally the refractive index of semiconductors. This work is concerned with the development of the methods of photonic crystal formation basing on CdS, CdTe and GaAs semiconductors. It was shown that complex refractive index of the CdS, CdTe and GaAs semiconductor samples is changed significantly after their modification. For example, the complex refractive index of CdS is changed from 2. 75 + i2.8113 up to 1.9 + i0.035. The real and imaginary parts of CdS refractive index are decreased by 0.85 and 2. 7763, respectively, while the absorption coefficient is decreased by 80 times. It is also shown that the interface between modified and non-modified sample areas is submerged into the sample depth (the distance from the surface being at least 11 μm). Thus, one- and two dimensional photonic crystals for visible and ultraviolet ranges can be effectively obtained using CdS, CdTe and GaAs semiconductor substrates by modifying thereof without complex lithographic technology.